Leisure-time physical activity, daily sitting time, and risk of mortality among CVD patients: a prospective cohort study - Xu, Changnan; Jin, Kai; Sun, Yike; Cai, Mengbiao; Zhu, Jian; Yang, Yi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease (CVD) is a leading cause of mortality globally. While leisure time physical activity (LTPA) and daily sitting time (DST) are known modulators of health, their combined impact on mortality risk specifically among CVD patients warrants further investigation. This study aimed to examine the independent and joint associations of LTPA and DST with mortality in a nationally representative sample of US adults with CVD.MethodsThis prospective cohort study included 2,335 adults with CVD (weighted mean age 61.56 years; 57.12% male) from the National Health and Nutrition Examination Survey (NHANES) 2007–2018, followed for a median of 5.75 years. LTPA was categorized as inactive (0 min/week), insufficiently active (1–<150 min/week), and sufficiently active (≥150 min/week). DST was categorized as 0–<6, 6–<8, and ≥8 h/days. Mortality data were obtained through linkage to the National Death Index until December 31, 2019. Cox proportional hazards models estimated hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for covariates.ResultsOver 14,139 person-years, 552 deaths (197 CVD-related) occurred. Sufficient LTPA (≥150 min/week) was associated with reduced risks of all-cause (HR: 0.45, 95% CI: 0.31–0.66, P < 0.001), CVD (HR: 0.51, 95% CI: 0.25–1.02, P = 0.058), and non-CVD mortality (HR: 0.43, 95% CI: 0.28–0.65, P < 0.001). Per 60 min/week increase in weekly LTPA was associated with 10% (HR: 0.90, 95% CI: 0.85–0.95) lower risk of all-cause mortality, 12% (HR: 0.88, 95% CI: 0.79–0.97) lower risk of CVD mortality, and 9% (HR: 0.91, 95% CI: 0.84–0.98) lower risk of non-CVD mortality, respectively. DST ≥8 h/days increased risks of all-cause (HR: 1.89, 95% CI: 1.50–2.37, P < 0.001), CVD (HR: 2.22, 95% CI: 1.51–3.26, P < 0.001), and non- CVD mortality (HR: 1.75, 95% CI: 1.29–2.36, P < 0.001) compared to <6 h/days. Combined analyses showed the lowest mortality risk in sufficiently active individuals with DST <6 h/days (all-cause HR: 0.27, 95% CI: 0.18–0.41, P < 0.001).ConclusionThis study suggests that increasing leisure-time physical activity and reducing sedentary time may have potential benefits for reducing mortality in patients with CVD.